Selection of Bandung City Travel Route Using The FLOYD-WARSHALL Algorithm - Arfananda, Muhammad Ghifari; Nasution, Surya Michrandi; Setianingsih, Casi (International Journal of Integrated Engineering, 2020)
The rapid development of information and technology, the city of Bandung tourism has also increased. However, tourists who visit the city of Bandung have problems in a limited time when visiting Bandung tourist attractions. Traffic congestion, distance and the number of tourist destinations to be a problem in tourists travel. The optimal route selection is the solution to the problem. Congestion and distance data are processed using the Simple Additive Weighting (SAW) method. Route selection uses the Floyd-Warshall Algorithm. In this study, the selection of the best route gets the smallest weight with a value of 5.127 from the Algorithm process. Based on testing, from two to five tourist attractions get an average calculation time of 3 to 5 seconds. This application is expected to provide optimal solutions for tourists in the selection of tourist travel routes.